2021
DOI: 10.3390/ijerph18020672
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes Associated with Latency in Late Preterm Premature Rupture of Membranes

Abstract: This study aims to evaluate the perinatal outcomes of preterm premature rupture of membrane (PPROM) with latency periods at 33 + 0–36 + 6 weeks of gestation. This retrospective case-control study included women with singleton pregnancies who delivered at 33 + 0–36 + 6 weeks at Korea University Ansan Hospital in South Korea between 2006–2019. The maternal and neonatal characteristics were compared between different latency periods (expectant delivery ≥72 h vs. immediate delivery <72 h). Data were compared am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Most of these complications occurred after 2 weeks from ROM. Our results are supported by a study done by Choi et al (28) in which the chorioamnionitis was diagnosed in (17.9%) in the expectant group versus (4.3%) in the immediate delivery group in women with PPROM after 34 weeks of gestation. Those results were consistent with a metaanalysis concluding that expectant management improved maternal and infant outcomes in late preterm PROM, specifically relating to maternal infection (10) .…”
Section: Discussionsupporting
confidence: 90%
“…Most of these complications occurred after 2 weeks from ROM. Our results are supported by a study done by Choi et al (28) in which the chorioamnionitis was diagnosed in (17.9%) in the expectant group versus (4.3%) in the immediate delivery group in women with PPROM after 34 weeks of gestation. Those results were consistent with a metaanalysis concluding that expectant management improved maternal and infant outcomes in late preterm PROM, specifically relating to maternal infection (10) .…”
Section: Discussionsupporting
confidence: 90%
“…We found that prolonged latency was unrelated to perinatal outcomes, Unlike chorioamnionitis, neonatal sepsis was not related to the duration of latency; this finding has also been confirmed by several other studies (27)(28)(29). Two studies revealed that a prolonged latency period was associated with a decreased incidence of neonatal mortality or morbidity (13,29).…”
Section: Discussionsupporting
confidence: 85%
“…However, another study showed that a prolonged latency period (≥72 h) did not increase maternal morbidities such as Chorioamnionitis ( 69 ). The disagreement between these studies could be attributed to variations in the sample size used, GA at delivery, maternal age, maternal social factors, and maternal comorbidities during pregnancy.…”
Section: Discussionmentioning
confidence: 99%